Blood Levels of Glutamate and Glutamine in Recent Onset and Chronic Schizophrenia - Madeira, Caroline; Alheira, Flavio V.; Calcia, Marilia A.; Silva, Thuany C. S.; Tannos, Filippe M.; Vargas-Lopes, Charles; Fisher, Melissa; Goldenstein, Nelson; Brasil, Marco Antonio; Vinogradov, Sophia; Ferreira, Sergio T.; Panizzutti, Rogerio (Frontiers in Psychiatry, 2018)
Converging evidence indicates that dysfunctions in glutamatergic neurotransmission and in the glutamate-glutamine cycle play a role in the pathophysiology of schizophrenia. Here, we investigated glutamate and glutamine levels in the blood of patients with recent onset schizophrenia or chronic schizophrenia compared to healthy controls. Compared with healthy controls, patients with recent onset schizophrenia showed increased glutamine/glutamate ratio, while patients with chronic schizophrenia showed decreased glutamine/glutamate ratio. Results indicate that circulating glutamate and glutamine levels exhibit a dual behavior in schizophrenia, with an increase of glutamine/glutamate ratio at the onset of schizophrenia followed by a decrease with progression of the disorder. Further studies are warranted to elucidate the mechanisms and consequences of changes in circulating glutamate and glutamine in schizophrenia.